Multiple jejunal perforations due to enteric fever: A case report from a rural tertiary care hospital india (Indian Journal of Case Reports, 2020)
Intestinal perforation is one of the most dreaded and common complications of the typhoid fever remarkably seen in developing countries which lead to diffuse peritonitis needing early surgical intervention. This is a case report of a 45-year-old male from a rural village of India presented to the emergency room with features of acute abdomen and intestinal obstruction. He underwent exploratory laparotomy and the findings were suggestive of multiple perforations due to enteric fever causing adhesive obstruction of the bowel due to peritonitis. Resection and jejunojejunal anastomosis were done as a part of the treatment. Thus, perforation occurring due to enteric fever should always be considered as a differential diagnosis in the patient presenting with an acute abdomen in rural areas where sanitary facilities are scanty.